Burden of prehypertension among adults in Kenya: a retrospective analysis of findings from the Healthy Heart Africa (HHA) Programme - Jared O. Mecha; Elizabeth N. Kubo; Collins O. Odhiambo; Freda G. Kinoti; Kennedy Njau; Gerald Yonga; Elijah N. Ogola (BMC, 2020)
Abstract Background Hypertension is the leading risk factor for mortality globally. African countries, including Kenya, have a high and rising prevalence of hypertension. Prehypertension is associated with an increased risk of progression to overt hypertension and a higher risk of cardiovascular disease and mortality. Despite this, little is documented on the prevalence and distribution of prehypertension in sub-Saharan Africa. This study sought to estimate the overall burden of prehypertension in Kenyan adults enrolled in a large hypertension control programme, Healthy Heart Africa. The distribution and determinants of prehypertension in the sample were explored as secondary objectives. Methods This was a post hoc analysis of cross-sectional data obtained from population-level blood pressure (BP) screening of adults aged ≥18 years in the community and ambulatory care facilities in 17/47 sub-national administrative units in Kenya. All participants with a complete record for systolic and diastolic BP were included. Descriptive analyses were performed for sociodemographic characteristics. Pearson's chi-square test was used to assess differences in categorical variables. Multivariate logistic regression analysis was performed to identify factors independently associated with prehypertension. Results Of 5,985,185 participant records that were included in the analysis, 34% were men (mean age: 45 [SD 2.9] years). The majority (63%) lived in rural Kenya. The prevalence of prehypertension was 54.5% and that of hypertension was 20.8%. Characteristics that were independently associated with prehypertension (adjusted odds ratio [95% CI]) included male sex (1.23 [±0.0023], p <  0.001 for all age groups > 25 years) and rural residence (1.60 [±0.023], p <  0.001). Conclusions Approximately one in every two Kenyan adults has prehypertension. This calls for urgent development and roll-out of a national BP screening and control programme. It also provides a strong basis for the formulation of multisectoral national policies that will ensure implementation of evidence-based, low-cost public health interventions geared towards primary prevention of hypertension, especially in population groups that are traditionally considered at low risk, such as young adults and rural residents.